Adopsi Teknologi Berbasis Smart Farming : Upaya Peningkatan Produktivitas Usahatani Padi di Nusa Tenggara Barat: Adopsi Teknologi Berbasis Smart Farming : Upaya Peningkatan Produktivitas Usahatani Padi di Nusa Tenggara Barat - Widhi Netraning Pertiwi; Migie Handayani; Sri Sari Utami (Journal Science Innovation and Technology (SINTECH), 2026)
The purpose of this study was to determine the increase in rice farming productivity carried out by farmers in West Nusa Tenggara Province, with the sample location being in Central Lombok Regency using the utilization of the Internet of Things (IoT). Technological developments in the agricultural world are essential to increase agricultural yields. The technology is in the form of soil and weather sensors that will measure in real time. With indicators measuring air temperature, soil pH, rainfall and soil moisture. Through these indicators connected to the internet, so that farmers can receive information obtained via smartphone. The number of samples used in this study was 75 rice farmers. The time used in this study was in MT I and MT II in 2023. The results of the study obtained a 260% increase in productivity from the production results obtained by farmers, while in MT I farmers still used conventional cultivation methods/what farmers usually do, the productivity obtained before using IoT was 2,082 kg/Ha and after using IoT was 7,502 kg/Ha. The results of the paired sample test showed a statistically significant increase in productivity after the implementation of IoT. Average productivity increased from 2,082 kg to 7,502 kg per growing season, with an average difference of 5,420 kg. The calculated t-value (t = 8.08, df = 74) shows statistical significance at the 5% level (p < 0.001). Furthermore, the effect size (Cohen's d = 0.93) indicates a large practical impact of IoT implementation on agricultural productivity. Based on the results of the t-test, it shows that there is a significant difference, so it can be concluded that the use of IoT in rice farming has a real impact on increasing productivity.